2021
DOI: 10.1177/08839115211022448
|View full text |Cite
|
Sign up to set email alerts
|

Structure and biological compatibility of polycaprolactone/zinc-hydroxyapatite electrospun nanofibers for tissue regeneration

Abstract: Although guided tissue regeneration (GTR) is a useful tool for regenerating lost tissue as bone and periodontal tissue, a biocompatible membrane capable of regenerating large defects has yet to be discovered. This study aimed to characterize the physicochemical properties and biological compatibility of polycaprolactone (PCL) membranes associated with or without nanostructured hydroxyapatite (HA) (PCL/HA) and Zn-doped HA (PCL/ZnHA), produced by electrospinning. PCL, PCL/HA, and PCL/ZnHA were characterized by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The addition of HA promotes a decrease in the endothermic melting enthalpies. Koupaei and Karkhaneh [53] and Pedrosa et al [54] reported the same behaviour in PCL/HA scaffolds and in PCL/HA membranes, respectively. These results can be explained due to the high crystallinity of HA that may alter the crystalline properties of the polymer and accelerate the nucleation of the PCL chain segments.…”
Section: Discussionmentioning
confidence: 63%
“…The addition of HA promotes a decrease in the endothermic melting enthalpies. Koupaei and Karkhaneh [53] and Pedrosa et al [54] reported the same behaviour in PCL/HA scaffolds and in PCL/HA membranes, respectively. These results can be explained due to the high crystallinity of HA that may alter the crystalline properties of the polymer and accelerate the nucleation of the PCL chain segments.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, the second peak close to 64 • C was attributed to another population of crystals not seen on the pure PCL fibre thermogram. Therefore, this peak could be assigned to PCL and propolis interactions, which favoured the formation of this more imperfect type of crystals [54].…”
Section: Thermal Behaviour Of Electrospun Matsmentioning
confidence: 95%
“…However, three stages of mass loss at higher temperatures were seen in the PCL/P. major electrospun mats, two of them with maximum DTG mass loss rate (peak maximum) at 181 and 256 °C, attributed to components of extract, and one between 320-450 °C related to the stage of PCL chain degradation [54,68].…”
Section: Thermal Behavior Of Electrospun Matsmentioning
confidence: 99%